Artikel Pemberian Oligosakarida Madu Alam Sebagai Prebiotik dalam Air Minum dan Pengaruhnya terhadap Performa dan Kesehatan Ayam Pedaging - Daud, Muhammad; Yaman, Muha Aman; Zulfan, Zulfan; Armia, Yasser; Wati, Tiara (JURNAL KAJIAN VETERINER, 2025)
One of the obstacles often faced in broiler farming is the decline in performance and disease attacks. Efforts that need to be made to improve health and prevent disease attacks are by increasing non-specific immune responses through the provision of feed additives such as prebiotics. Prebiotics are non-digestible compounds and function as a food source for good microorganisms in the digestive tract. One such source is natural honey which contains oligosaccharides so that it acts as a prebiotic. The purpose of the study was to evaluate the provision of drinking water containing natural honey oligosaccharides to improve the performance and health of broiler. The research was conducted experementally using a completely randomized design (CRD) consisting of four treatments and the replications. The research treatments included: P0:control, P1:0.5% natural honey oligosaccharides (v/w), P2:1% natural honey oligosaccharides (v/w), and P3:1.5% natural honey oligosaccharides (v/w). The research variables include: ration consumption, body weight gain, final body weight, ration conversion, ration efficiency, drinking water consumption, mortality, feces shape and feces color. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test. The results indicated that ration consumption, body weight gain, final body weight and ration efficiency, drinking water consumption, and health increased in the treatment containing natural honey oligosaccharides and decreased in the ration conversion and mortality of broiler relative to the control. The study concluded that the provision of drinking water containing honey oligosaccharides as prebiotic of 0.5 to 1.5% improved both the performance and health status of broiler.